Long-Term Outcomes Following Bilateral vs Single Internal Thoracic Artery Grafts - David P. Taggart; Mario Gaudino; Stephen Gerry; Marek Jasinski; Belinda Lees; Alastair M. Gray; Vipin Zamvar; Marek Deja; Siven Seevanayagam; Fernando Ribeiro de Moraes Neto; Janusz Konstanty-Kalandyk; Rafal Pawlaczyk; et al. (JAMA Cardiology, 2026)
Importance Bilateral internal thoracic artery grafting has been proposed to improve survival compared to standard single internal thoracic artery grafting during coronary artery bypass graft (CABG) surgery, but any survival benefit may emerge only with longer-term follow-up. Objective To report 15-year extended follow-up of a randomized clinical trial of bilateral vs single internal thoracic artery grafting for CABG. Design, Setting, and Participants This is a secondary analysis of an unblinded randomized clinical trial that took place at 28 cardiac surgery centers in 7 countries between June 2004 and December 2007, with 15-year follow-up reported after 2025. Patients scheduled for CABG on clinical grounds were eligible. Those requiring only single grafts or concomitant valve surgery, as well as those with a history of previous CABG, were excluded. All 3102 patients in the original trial provided data for this analysis, while 3042 completed the full 15-year follow-up. Data were analyzed from January to March 2026. Intervention If patients fulfilled all the eligibility criteria and provided written informed consent, they were randomly assigned to bilateral or single internal thoracic artery grafts with vein or radial artery grafts used in both groups as clinically indicated. Main Outcomes and Measures All-cause mortality at 15 years. The composite of all-cause mortality, myocardial infarction, or stroke was a secondary outcome. Results A total of 1548 patients were randomized to bilateral internal thoracic artery grafts and 1554 to single internal thoracic artery grafts. The mean (SD) age was 64 (9) years and 446 (15%) were female. In the bilateral graft group, 215 (14%) received only a single arterial graft, while in the single graft group, 359 (23%) also received a radial artery graft. At 15 years, vital status was known for 3039 patients (98%). There were 585 deaths (37.8%) in the bilateral graft group and 584 (37.6%) in the single graft group (hazard ratio [HR], 1.00; 95% CI, 0.89-1.12; P = .97). Secondary outcome event rates were 43.9% and 45.8%, respectively (HR, 0.94; 95% CI, 0.85-1.05). Conclusions and Relevance There was no difference in all-cause mortality at 15 years between patients undergoing CABG who were randomized to bilateral vs single internal thoracic artery grafts in an intention-to-treat analysis. Given the high rate of potential postrandomization confounders (eg, crossovers and use of radial arteries), the multiple arterial graft hypothesis still needs to be tested in randomized clinical trials. Trial Registration isrctn.org Identifier: ISRCTN46552265